Current agritourism literature: What methods did researchers prefer? - Starman Ana; Pavić Lazar (Glasnik Srpskog Geografskog Društva)
Agritourism is a common diversification strategy of farms and an important research topic, especially considering sustainable rural development. This study analysed current scientific literature (2019-2023) in the field of agritourism from the perspective of methodology. Publications from five scientific journals which were identified as the most relevant for this field of research, were analysed. Articles with keywords agritourism or agri-tourism in the title were selected and a sample of 53 articles was identified. Articles were grouped into studies focused on secondary data analysis and original studies which were further categorized based on research choices, primary data collection methods and sampling techniques. It was found that 10 articles focused on secondary data analysis, whilst more than 80% of research was original. More than half of original scientific studies opted for quantitative data collection and analysis, followed by qualitative methods (28%), mixed model (9%) and mixed methods (7%). The questionnaire method was identified as the main data collection technique in current agritourism literature. Although, pilot testing was rarely conducted. Current literature on agritourism doesn’t seem to be focused on generalising the findings, as non-probability sampling techniques were more frequently selected than probability sampling. Other than questionnaires, in-depth interviews, structured observation, participant observation and semi-structured interviews were used for collecting data. However, the type of interview or observation were not always specified. Approximately 13.2% of publications in the sample researched agritourism from an international context. By reviewing current agritourism literature, our aim was to present its focus from the methodology perspective, thus contributing to a clearer understanding of research directions in the agritourism scientific field.